Infectivity and Persistence of Ss Nematodes on Pasture Mole Crickets in South-Central Florida - Martin B. Adjei; Grover C. Smart, Jr.; Byron J. Adams (EDIS)
This document is ENY-669, one of a series of the Entomology and Nematology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Original publication date August 2002.